Adolescent attachment in Nepal: Testing the factorial validity of two scales. Issue 4 (4th July 2017) - Sochos, Antigonos; Lokshum, Chetana
Abstract: Attachment theory is an important framework in the psychology of human development and has direct relevance to the study of adolescence. The cross-cultural validity of attachment constructs and measures has been the subject of lively debate among experts. Using confirmatory factor analysis, the present study tested the factor structure of the Adolescent Attachment Questionnaire and the Adolescent Unresolved Attachment Questionnaire in a sample of 279 Nepali adolescents. The hypothesised models had a good fit and further tests established the measurement invariance of the two instruments. The cross-cultural validity of the measures was supported but areas of cultural variation were also highlighted.